PERAN BUDAYA DALAM KEHidUPAN BERAGAMA KAJIAN ATAS KEHIDUPAN BERAGAMA UMAT KATOLIK SUNDA DI CIGUGUR - Cornelius Iman Sukmana (P3TK, Sanata Dharma University, 2014)
Religious life is directly related to cultural life. This is observable among Sundanese Catholics in Cigugur. In religious life, the respective Sundanese culture strongly marked its influence. The way one lives his or her religiosity also reflects their culture. It is common that religious people live together with other people of different religious belief and practices. In this context culture helps them to be able to live harmoniously with people from different religions. This article focuses on the history of the Catholic community in Cigugur, Kuningan while inquiring the role of the Sundanese culture in their daily life within their Catholic community.